Entre a matriz portuguesa e a literatura nacional: a concepção de texto literário para João Ribeiro - Bulhões, Ricardo Magalhães; Ferreira, Eliane Aparecida Galvão Ribeiro [UNESP] (My University, 2012)
This paper aims at rescuing some critical appraisals found in the high school anthology Autores Contemporâneos (1931), by the critic, philologist and writer João Ribeiro, one of the main Brazilian intellectual representatives of the first decades of the twentieth century. João Ribeiro, along with Coelho Neto and, Laudelino Freire, among others, took part in of the panel which compiled, in 1921, the Dicionário da Academia Brasileira de Letras. Therefore, we find the analytical process João Ribeiro, their theoretical observations, concepts and dilemmas which are appointed by him in literary history and criticism of the early twentieth century.

O presente texto tem como objetivo resgatar algumas apreciações críticas presentes na antologia escolar Autores Contemporâneos (1931), do crítico, filólogo e escritor João Ribeiro, uma das figuras mais importantes da intelectualidade brasileira nas primeiras décadas do século XX. João Ribeiro, ao lado de Coelho Neto e Laudelino Freire, entre outros, participou da comissão que elaborou, em 1921, o Dicionário da Academia Brasileira de Letras. Para tanto, verificaremos o processo analítico de João Ribeiro, suas observações teóricas, seus conceitos e quais impasses são por ele apontados na história literária e na crítica do início do século XX.
Between portuguese’s matrix and national literature: the João Ribeiro’s conception of literary text
Keywords: Literature; High School Anthology; Literary History; Deadlocks; Literatura; Antologias; História Literária; Impasses